(4/9+3/4) x 2/4 + 6/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Học sinh nhẩm và ghi kết quả như sau:
3 x 4 = 12 2 x 6 = 12 4 x 3 = 12 5 x 6 = 30
3 x 7 = 21 2 x 8 = 16 4 x 7 = 28 5 x 4 = 20
3 x 5 = 15 2 x 4 = 8 4 x 9 = 36 5 x 7 = 35
3 x 8 = 24 2 x 9 = 18 4 x 4 = 16 5 x 9 = 45
3 x4 = 12
3 x7 = 21
3 x5 = 15
3 x8 =24
2 x 6= 12
2 x8 = 16
2 x4 =8
2 x9 =18
4 x3 =12
4 x7 =28
4 x9 =36
4 x4 =16
5 x6 =30
5 x4 =20
5 x7 =35
5 x9 =45
= 51/20
----------------------------------
= 3/14
------------------------------------
= 4/7 - 2/7
= 2/7
--------------------------------------
= 17/45
---------------------------------------
= 2/3
--------------------------------------
= 2 x 1/4
= 1/2
\(\dfrac{37\cdot5^4}{25^2}=\dfrac{37\cdot5^4}{5^4}=37\\ \dfrac{2^4\cdot2^6\cdot3^8\cdot9^2}{4^4\cdot3^{11}}=\dfrac{2^{10}\cdot3^8\cdot3^4}{2^8\cdot3^{11}}=2^2\cdot3=12\\ \dfrac{3\cdot9^4\cdot9^3}{3^2\cdot9}=\dfrac{3\cdot3^8\cdot3^6}{3^2\cdot3^2}=3^{11}\\ \dfrac{125\cdot5\cdot64-25^3\cdot10\cdot4}{5^7\cdot8}=\dfrac{5^3\cdot5\cdot2^6-5^6\cdot2\cdot5\cdot2^2}{5^7\cdot2^3}=\dfrac{5^4\cdot2^3\left(2^3-5^3\right)}{5^7\cdot2^3}=\dfrac{8-125}{5^3}=\dfrac{-117}{125}\)
a) 2 x 2 = 4 3 x 3 = 9
2 x 4 = 8 3 x 5 = 15
2 x 6 = 12 3 x 7 = 21
2 x 8 = 16 3 x 9 = 27
4 x 4 = 16 5 x 5 = 25
4 x 2 = 8 5 x 7 = 35
4 x 6 = 24 5 x 9 = 45
4 x 8 = 32 5 x 3 = 15
b) 200 x 4 = 800 300 x 2 = 600
200 x 2 = 400 300 x 3 = 900
400 x 2 = 800 500 x 1 = 500
100 x 4 = 400 100 x 3 = 300
`@` `\text {Ans}`
`\downarrow`
`1)`
\(x+\dfrac{1}{2}=\dfrac{5}{3}\)
`\Rightarrow` \(x=\dfrac{5}{3}-\dfrac{1}{2}\)
`\Rightarrow`\(x=\dfrac{7}{6}\)
Vậy, `x =`\(\dfrac{7}{6}\)
`2)`
\(\dfrac{3}{5}-x=\dfrac{1}{3}\)
`\Rightarrow`\(x=\dfrac{3}{5}-\dfrac{1}{3}\)
`\Rightarrow`\(x=\dfrac{4}{15}\)
Vậy, `x =`\(\dfrac{4}{15}\)
`3)`
\(\dfrac{3}{4}+x=\dfrac{7}{2}\)
`\Rightarrow`\(x=\dfrac{7}{2}-\dfrac{3}{4}\)
`\Rightarrow`\(x=\dfrac{11}{4}\)
Vậy, \(x=\dfrac{11}{4}\)
`4)`
\(x-\dfrac{4}{3}=\dfrac{7}{9}\)
`\Rightarrow`\(x=\dfrac{7}{9}+\dfrac{4}{3}\)
`\Rightarrow`\(x=\dfrac{19}{9}\)
Vậy, `x=`\(\dfrac{19}{9}\)
`5)`
\(x-\dfrac{5}{6}=\dfrac{7}{3}\)
`\Rightarrow`\(x=\dfrac{7}{3}+\dfrac{5}{6}\)
`\Rightarrow x =`\(\dfrac{19}{6}\)
Vậy, `x=`\(\dfrac{19}{6}\)
`6)`
\(x-\dfrac{1}{5}=\dfrac{9}{10}\)
`\Rightarrow x=`\(\dfrac{9}{10}+\dfrac{1}{5}\)
`\Rightarrow x=`\(\dfrac{11}{10}\)
Vậy, `x=`\(\dfrac{11}{10}\)
- \(x\cdot2\frac{4}{9}=4\frac{2}{5}-1\frac{4}{7}\)
\(x\cdot\frac{22}{9}=\frac{22}{5}-\frac{11}{7}\)
\(x\cdot\frac{22}{9}=\frac{99}{35}\)
\(x=\frac{99}{35}:\frac{22}{9}\)
\(x=\frac{81}{70}\)
Vậy \(x=\frac{81}{70}\).
- \(x:10\frac{6}{5}=4\frac{6}{5}+9\frac{7}{5}\)
\(x:\frac{56}{5}=\frac{26}{5}+\frac{52}{5}\)
\(x:\frac{56}{5}=\frac{78}{5}\)
\(x=\frac{78}{5}\cdot\frac{56}{5}\)
\(x=\frac{4368}{25}\)
Vậy \(x=\frac{4368}{25}\).
- \(x:3\frac{10}{3}=9\frac{1}{9}-5\frac{1}{9}\)
\(x:\frac{19}{3}=4\)
\(x=4\cdot\frac{19}{3}\)
\(x=\frac{76}{3}\)
Vậy \(x=\frac{76}{3}\).
1.
\(8\times8=64\)
\(6\times4=24\)
\(4\times4=16\)
2.
Ta có:
\(4\times6=24\) \(7\times5=35\)
Vì \(24< 35\) nên \(4\times6< 7\times5\)
Vậy...
_____
Ta có:
\(5\times7=35\) \(8\times9=72\)
Vì \(35< 72\) nên \(5\times7< 8\times9\)
Vậy....
_____
Ta có:
\(3\times5=15\) \(6\times9=54\)
Vì \(15< 54\) nên \(3\times5< 6\times9\)
Vậy...
\(#Wendy.Dang\)
8 x 8 =64
6 x 4 =24
4 x 4=16
Bài 2 : < , > , =
4 x 6 < 7 x 5
5 x 7 < 8 x 9
3 x 5 < 6 x 9
a: =91/105+60/105-101/105
=50/105=10/21
c: \(\dfrac{3}{4}\cdot\dfrac{5}{2}\cdot\dfrac{7}{6}=\dfrac{3}{6}\cdot\dfrac{7}{2}\cdot\dfrac{5}{4}=\dfrac{1}{2}\cdot\dfrac{7}{2}\cdot\dfrac{5}{4}=\dfrac{35}{16}\)
d: =2-2/9
=18/9-2/9
=16/9
e: =24/36-9/36+8/36
=23/36
g: =5/2+1/2
=3
(4/9+3/4) x 2/4 + 6/4=151/72